Pembelajaran Kewirausahaan dan Motivasi Siswa terhadap Minat Berwirausaha Pada Siswa Kelas XI SMK Negeri 1 Keruak: Entrepreneurship Learning and Student Motivation towards Entrepreneurial Interest in Class XI Students of SMK Negeri 1 Keruak - Irwan Yon Hadi (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2025)
Entrepreneurship is a process of carrying out new, creative, different, or innovative activities in an effort to obtain something for oneself and provide added value to society. The purpose of this study was to determine how much influence entrepreneurship learning and motivation have on entrepreneurial interest in class XI students of SMK Negeri 1 Keruak in terms of individual parameter significance and simultaneous significance. This study was conducted at SMK Negeri 1 Keruak on 65 respondents as research samples. The type of research used is ex post facto with a quantitative approach. The sampling technique used is simple random sampling while data collection uses questionnaire and documentation techniques. data analysis methods using a Likert scale. The variables proposed are entrepreneurship learning and motivation. The results of this study indicate that (a) entrepreneurship learning has a significant effect on entrepreneurial interest in class XI students of SMK Negeri 1 Keruak. (b) motivation has a significant effect on entrepreneurial interest in class XI students of SMK Negeri 1 Keruak. (c) Entrepreneurship learning and motivation have a significant effect on entrepreneurial interest in class XI students of SMK Negeri 1 Keruak because it has a value of 0.000 on entrepreneurial interest in class XI students of SMK Negeri 1 Keruak which means it has a significant effect on entrepreneurial interest. The Determination Coefficient (R Square) is 0.519, which shows that entrepreneurship learning and motivation significantly affect the entrepreneurial interest of class XI students of SMK Negeri 1 Keruak by 51.9%, while the remaining 48.1% is influenced by other variables outside the model.